Religious Values ​​and Filial Piety: The Short Story of the Shopper on Mother's Orders and the Relevance to Indonesian Language Learning - Saptiana Sulastri; Aurel Aulia Salsabila; Juliawati; Siska Arini Putri; Widya Azhari; Ramadhan Kusuma Yuda (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
An article titled “Religious Values and Filial Piety in the Short Story Tukang Belanja Suruhan Ibu and Its Relevance to Indonesian Language Education.” This study aims to describe the religious values and filial piety toward parents in the short story Tukang Belanja Suruhan Ibu by Silawati and to analyze its relevance to Indonesian language instruction in elementary schools. The object of the study is the text of the short story Tukang Belanja Suruhan Ibu. The population in this study is the entire text of the short story, while the sample consists of excerpts of dialogue and narration containing religious values and filial piety toward parents. The research instrument used was the researcher herself, assisted by a data recording sheet. Data collection was conducted through intensive reading and note-taking. Data analysis employed a qualitative descriptive method using a content analysis approach. The results of the study indicate the presence of religious values such as trustworthiness, honesty, and gratitude, as well as values of filial piety toward parents, including obedience, mutual aid, responsibility, and efforts to restore trust. These values are relevant for integration into Indonesian language education, particularly in children’s literary appreciation and the character development of students.